2021
DOI: 10.1186/s13075-021-02649-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of systemic lupus erythematosus on the 5-year survival of critically ill septic patients

Abstract: Background Infectious disease is an increasing threat to patients with systemic lupus erythematosus (SLE); however, the long-term outcome in critically ill septic patients with SLE remains unclear, and we aimed to address the impact of SLE on 5-year survival in critically ill septic patients. Methods We used the 2003–2017 nationwide data with 825,556 patients with sepsis in Taiwan. We identified lupus cases with sepsis that required admission to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…SLE is a chronic multisystem AID characterized by a broad range of laboratory and clinical manifestations. [32,33] Patients with SLE were more likely to succumb to sepsis than non-SLE patients. [25] Moreover, sepsis patients with SLE were observed to have a higher short-term mortality and unfavorable long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SLE is a chronic multisystem AID characterized by a broad range of laboratory and clinical manifestations. [32,33] Patients with SLE were more likely to succumb to sepsis than non-SLE patients. [25] Moreover, sepsis patients with SLE were observed to have a higher short-term mortality and unfavorable long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[6,25] As opposed to that, a population-based case-control study conducted by Chen HH et al revealed that SLE was linked to a higher long-term (5 years) mortality rate in patients with severe sepsis requiring ICU admissions and mechanical ventilation. [33] Surprisingly, Oud, L. and J. Garza contradicted these ndings by suggesting that SLE was associated with a reduced risk-adjusted odds of short-term mortality, and they contended that the increased likelihood of developing sepsis, rather than the higher fatality rate among SLE patients, was the primary driver of the elevated risk of sepsis-related short-term mortality related to sepsis. [8] The con icting ndings mentioned above may be attributed to various factors, including the size of the sample, potential bias in sample selection, cytokine levels at baseline, the use of steroids and immunosuppressive drugs, the severity of sepsis, the methods employed to estimate the cohort's outcome after adjusting for risk, and others.…”
Section: Discussionmentioning
confidence: 99%